Nonpuerperal Breast Infection. Issue 2 (1995) - Casas, C. Miranda; Pérez, M.; Alados, J. C.; Fontes, J.; Orellana, G.; Aguilar, J. M.; Miranda, J. A.; de la Rosa, M.
Abstract : Objective: We undertook a microbiological study of purulent specimens from women with symptomatic breast abscesses. Methods: Fifty-one purulent samples were collected in 2 periods (December 1991–April 1992 and January 1994–June 1994) from nonpuerperal breast abscesses in 44 patients attending our hospital. Results: One of the most frequently isolated microorganisms was Proteus mirabilis (9 patients, 20.4%), present as a pure culture in all but 1 specimen (isolated together with Peptostreptococcus spp.). Staphylococcus aureus was isolated in 10 specimens, 6 of which were post-tumorectomy abscesses. Polymicrobial anaerobic flora were isolated in 11 specimens (21.5%); Staphylococcus epidermidis in 4 (8%); and Streptococcus milleri, Alcaligenes sp., and mixed aerobic-anaerobic flora in 1 specimen each. The 7 remaining samples (13.7%) were negative bacteriological cultures. Conclusions: We draw attention to the frequent isolation of P. mirabilis in recurrent and torpid breast abscesses in 4 women in whom surgery was necessary in addition to antibiotic treatment.